Diversity of medicinal plants utilized by To Manui ethnic of Central Sulawesi, Indonesia - Nuning Rahmawati; FANIE INDRIAN MUSTOFA; SARI HARYANTI (Society for Indonesian Biodiversity, 2020)
Abstract. Rahmawati N, Mustofa FI, Haryanti S. 2020. Diversity of medicinal plants utilized by To Manui ethnic of Central Sulawesi, Indonesia. Biodiversitas 21: 375-392. The present study reports the utilization of medicinal plants as medicines for the treatment of various diseases among the people of To Manui tribe in Central Sulawesi Province of Indonesia. Data collecting was conducted based on purposive random sampling to five selected traditional healers who fulfilled some inclusion criteria. The results showed as of 89 species of medicinal plants distributed in 50 families and 80 genera have been documented to have any pharmacological effects against 37 diseases and illnesses. Curcuma longa L. was determined as the most frequent medicinal plant used by traditional healers in To Manui for treating diabetes mellitus as well as after-birth treatment. However, conservation of some medicinal plants needs to be initiated in the study area especially Alstonia scholaris (L.) R. Br. as it is recognized in International Union for Conservation of Nature (IUCN) Red List as Least Concern (LC) of conservation status.